Improving spatial predictions of Eucalypt plantation growth by combining interpretable machine learning with the 3-PG model - Taylor, Peter; Almeida, Auro C.; Kemmerer, Ernst; Abreu, Rafael Olivares de Salles (Frontiers in Forests and Global Change, 2023)
Accurate predictions of forest plantation growth provide forest managers with improved forest inventory estimates, forest valuation and timely harvest schedules. Forest process-based models are increasingly used for quantifying current and potential productivity, yield gaps and factors limiting growth, such as climate variability, soil characteristics, and water deficit. Improvements in the availability and resolution of spatial and temporal data combined with advancements in machine learning algorithms provide new opportunities to improve model predictions. This study shows how interpretable machine learning (ML) can be used to independently predict site soil fertility rating (FR) and incorporate these results into the 3-PG forest process-based model to accurately predict plantation growth. Four ensemble decision tree machine learning models - random forest trees, extremely randomised trees, gradient boost, and XG boost - were trained and compared using spatial cross-validation across the study area. FR predictions were estimated in relation to the influencing soil type and terrain characteristics, and interpretable ML methods were used to show how input feature permutations may relate to the soil fertility predictions. Results show the explanatory variables are similar across the selected ML models, with the strongest influencing variables being a water leaching index, site aspect, and the silt and sand soil texture properties. The extremely randomised tree models showed the overall best performance, with only small variation in performance across the four ML models. The method was applied to Eucalyptus nitens plantations covering over 63,000 ha in north-west Tasmania, Australia. Results using the predicted FR spatial grid with 3-PG show strong correlation with observed growth for tree diameter and stand volume (R2 tree diameter at breast height = 0.97, RMSE = 0.85m; R2 stand volume = 0.96, RMSE = 23.1m3 ha-1) obtained from 161 permanent sample inventory plots ranging from 3 to 31 years old. This method has practical utility for other study sites to calibrate forest plantation soil fertility rating, in both the spatial and point-scale 3-PG model, where spatial data of soil characteristics are available. The derived soil fertility grid can provide valuable insights into the spatial variability of soil fertility in unknown areas.